2021
DOI: 10.1177/2333721421999279
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Changes in Caregiver Burden and Caregiving Intensity due to COVID-19

Abstract: This study explored self-reported changes in caregiving intensity (CI) and caregiver burden (CB) among informal caregivers due to the COVID-19 pandemic overall and by gender. Informal caregivers for someone age 50+ completed a survey via Amazon’s MTurk in June 2020. Participants reported changes in CI and CB due to COVID-19 and provided demographic information. Multinomial logistic regression models assessed changes in CI and CB attributed to the COVID-19 pandemic overall and by gender. The sample ( n = 835) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
109
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 49 publications
16
109
1
Order By: Relevance
“…The majority reported experiencing increases in caregiving intensity (55.7%) and caregiver burden (53.1%). 42 A closer examination of the data found that, as in caregiving experiences outside of the pandemic, there were notable differences by gender. Women were more likely than men to experience increases in both aspects of caregiving during the pandemic, 42 which reflects overall patterns of females shouldering a disproportionate amount of both caregiving responsibilities and impacts on their health and well-being.…”
Section: Informal Caregiving During the Covid-19 Pandemicmentioning
confidence: 99%
“…The majority reported experiencing increases in caregiving intensity (55.7%) and caregiver burden (53.1%). 42 A closer examination of the data found that, as in caregiving experiences outside of the pandemic, there were notable differences by gender. Women were more likely than men to experience increases in both aspects of caregiving during the pandemic, 42 which reflects overall patterns of females shouldering a disproportionate amount of both caregiving responsibilities and impacts on their health and well-being.…”
Section: Informal Caregiving During the Covid-19 Pandemicmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) has been recognized as a Public Health Emergency of International Concern by the World Health Organization [1]. Restrictive measures, such as social distancing, the use of face masks, and mobility restrictions, have been adopted by governments worldwide to reduce the spread of the virus [2], drastically altering people's lives [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the overload of activities led to an increase in stress and burden among caregivers [ 16 ]. Studies revealed that, during the COVID-19 pandemic, care providers exhibited a decrease in physical and mental health [ 12 ], and that social isolation heavily affected multiple aspects of the quality of life of caregivers [ 17 , 18 ], including an increase in depression and anxiety [ 19 ], besides compromising their ability to take care of others [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several published studies have pointed out the worsening in the care situation during COVID-19 pandemic [ 43 , 47 , 48 ]. However, the relationship between caregiving and mental health outcomes has been mainly analyzed in a comparative, descriptive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Informal caregiving, which is defined as the unpaid care provided to dependent relatives or family members [ 42 ], seems to increase even more the psychological consequences of the COVID-19 pandemic. Greater levels of anxiety, depression and even somatic symptoms have been found in this population [ 40 , 43 , 44 , 45 , 46 ], while its caregiving intensity and burden increased during this period [ 47 , 48 ]. Due to the complete closure of day-care centers, the loss of support services and the saturation of healthcare capacities, informal caregivers had played an even more important role during COVID-19 pandemic [ 43 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%